System value and progress of CSP. (August 2017) - Gauché, Paul; Rudman, Justine; Mabaso, Mbalenhle; Landman, Willem A.; von Backström, Theodor W.; Brent, Alan C.
Highlights: CSP capacity to end of 2016 is almost 5 GW, slower than hoped, but 5 GW in Chinese plans. Evidence of learning rate does exist once sufficient similar capacity added without delay. Energy systems analysis is evolving with recent large-scale utility renewables including CSP. System value of CSP relates to storage and dispatch, but uptake is likely more complex. Marginal system value methods need to capture spatiotemporal behavior to determine value. Abstract: Concentrating solar power (CSP) offers the value proposition of being a baseload and dispatchable renewable energy technology. CSP significantly lags behind solar photovoltaic (PV) and wind power by cumulative capacity and cost for a number of reasons including the complicated nature of the technology and the traditional inability of the technology to be economically viable at smaller scales. The scaling limitation itself has prevented the technology from learning faster due to limited market share, which has inhibited the learning rate and continued to make CSP project financing difficult due to finance quantum risks. CSP has limited but successful lifecycle experience due to the SEGS I–IX plants commissioned between 1985 and 1990 in California. More recently, the technology benefited from competitive tariffs before the adoption of PV and learning rates undermined its growth. PV (as with wind) now offers some of the lowest electricity generating rates of any technology. While this is valuable, the marginal value of intermittent renewables is roughly inversely proportional to their share of the electricity system as their capacity credit diminishes with each addition to capacity, all other things equal. CSP with storage has the ability to flexibly deliver electricity and to do so 24 h a day in the right conditions. CSP plants with up to 15 h of full-load storage have now been commissioned and are demonstrating initial evidence that they can deliver to expectation. Despite the proposed value of CSP, it is not penetrating the market as expected. The value of electricity has simply not been valued for instance in the U.S. market to date, which has valued renewable targets above capacity needs. Sunny developing countries have been identified as potential growth markets due to capacity constraints and the avoided cost of electricity. Most recently, China has embarked on the greatest capacity growth of CSP in the decision to commission around 5 GW of CSP within the next 5 years with 1.35 GW assigned to be online by the end of 2018. Even with this evolution, CSP will still significantly lag other renewables. This review covers the system value and progress of CSP. An overall description of CSP and its value is followed by a broad review of CSP experience and research. A review of CSP in energy systems analysis is then provided to expose and quantify the marginal value of CSP. It is argued that improved quantification and accuracy in terms of energy systems analysis is an important step for CSP growth. The findings from the review show that CSP has potential to be the backbone of future electricity systems, but it needs to demonstrate value and acceptance to a broader audience than might be expected to achieve this.